Il tema della luce in alcuni testi di Sant’Agostino e di San Bonaventura - Barrajón, L.C., Amador Pedro (Alpha Omega, 2021)
Summary: The article deals with the topic of light in some important authors of Christian Tradition, St. Augustine and St. Bonaventure. St. Augustine considers the light from a metaphysical point of view. The divine light enables man to know the mutable world with truth and certitude. Otherwise, the human knowledge would not be founded on solid grounds. St. Bonaventure considers in some of his writings the light of physical bodies as ontological part of their being. For him light is like a substantial form, that qualifies the essence of a physical being. In these two authors we can see the importance of the concept of light in Christian tradition; in the case of St. Augustine, for the foundation of knowledge; in the case of St. Bonaventure for the metaphysical constitution of physical beings. Key words: Light, illumination, St. Augustine, St. Bonaventure, creation, substantial form, metaphysics of light. Parole chiave: Luce, illuminazione, Sant’Agostino, San Bonaventura, creazione, forma sostanziale, Metafisica della luce.